Role of Debt Maturity Structureon Firm Fixed Assets During Sudden Stop Episodes : Evidence From Thailand - Morsy, Hanan; Iannariello, Maria Pia.; Terada-Hagiwara, Akiko (Washington, D.C. : International Monetary Fund, 2007)
This paper studies the detrimental effect of sudden stops on the growth of Thai firms' fixed assets. We focus on the fixed assets adjustment that firms undertake at times of financial constraints. We derive our results from balance sheet data for 284 nonfinancial Thai listed firms. Our data demonstrate that Thai firms faced severe declines in the growth of their fixed assets starting in 1996. Regression results demonstrate, after controlling for firms' characteristics and lagged dependent variables, that holding longer-term debt maturity structure is the factor that works in the firms' favor during sudden stop episodes, while it is their profitability that matters during tranquil periods.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet